Comparative study on the Chemical composition and antibacterial activity of the essential oil of Chromolaena laevigata (Lam.) R.M. King & H. Rob. collected from Mérida-Venezuela. - Rojas, Janne; Suárez, Fabiola; Bueno, Daniela; Buitrago, Alexis; Rojas, Luis; Velazco, Elsa (Ciencia)
Fresh leaves of C. laevigata collected from the same location in January (Jan), July (Jul) and December (Dec) 2010 were analyzed by GC/MS. The main compounds of the Jan sample were lae- vigatine (59.60%), germacrene-D (7.75%) and ï¿½-sesquiphellandrene (6.56%), for the Jul oil laeviga- tine (62.61%), germacrene-D (7.37%), ï¿½-sesquiphellandrene (6.67%) and ï¿½-caryophyllene (5.39%), while Dec sample showed laevigatine (44.05%), ï¿½-sesquiphellandrene (8.59%) and ï¿½-caryophyllene (5.96%) as major components. Antibacterial assays showed activity against E.faecalis (1000 µg/mL), S. aureus (25 µg/mL) and S. aureus methicilline resistant (1000 µg/mL).